Retos Americana Emprendedora 2018-2025 - Gómez Núñez, Liyis (Corporación Universitaria Americana, 2018)
Americana Emprendedora is a strategy to generate value, not only for the particular benefit of the institution and its direct stakeholders - students, alumni, faculty and staff at all levels - but also for their families, the region and the country. This is because we are convinced of the impact of entrepreneurship as an engine of economic and social development of individuals and communities.